Antibacterial Efficiency In The Hemolymph Of Black Ant, Camponotus Compressus - PRADEEP PADMANABHAN,; REVATHY GOPALAKRISHNAN,; KASINATHAN KALIMUTHU, (International Journal of Pharma and Bio Sciences, 2012)
The hemolymph of Camponotus compressus was screened for antibacterial activity against clinically important bacterial species (Kleibsiella pneumonia MTCC 109, Vibrio cholera ATCC 14035, Micrococcus luteus ATCC 4698 and Staphylococcus aureus MTCC 96) using agar well diffusion method. The C. compressus hemolymph showed strong activity against the susceptible strains S. aureus MTCC 96 and K. pneumonia MTCC 109. The hemolymph exhibited considerable inhibitory effects against all the pathogenic organisms under test while their major components demonstrated various degrees of growth inhibition. Literature survey of Camponotus compressus revealed that no researcher has yet reported anti bacterial activities of C. compressus. Therefore, it is worth conducting an investigation on the anti bacterial activity of an ant species, C. compressus.